A high-performance cellulose welding rod coating, welding rod and preparation method thereof
By combining modified carboxymethyl cellulose and konjac powder, the composition of cellulose electrode powder is improved, and the problems of insufficient arc blowing, poor stability and poor weld mechanical properties are solved, and the enhancement of arc blowing of welding rods, improvement of thermal stability and improvement of weld mechanical properties are achieved.
Patent Information
- Application Number
- CN202411293450.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-09-14
AI Technical Summary
During the use of existing cellulose electrodes, there are problems such as insufficient arc blowing, poor stability and poor mechanical properties of the weld.
By improving the composition of the electrode powder, and using modified carboxymethylcellulose and konjac powder, the arc blowing and thermal stability of the electrode are improved and the mechanical properties of the welds are improved.
The enhancement of the arc blowing force of the welding rod, the improvement of thermal stability and the improvement of the mechanical properties of the welds are achieved, and the demand for high-performance welding rods is met.
Smart Images

Figure BDA0005045264160000081 
Figure BDA0005045264160000091 
Figure BDA0005045264160000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal welding, and in particular to a high-performance cellulose welding rod coating, a welding rod and a preparation method thereof. Background Art
[0002] Pipeline welding technology is to connect different pipeline components together to form a complete pipeline system, which is widely used in the fields of petroleum, chemical industry, etc. In pipeline construction, pipeline welding is very important, and welding rods play an important role in welding.
[0003] Cellulose welding rods are acidic welding rods with more organic matter in the coating. Compared with ordinary welding rods, cellulose welding rods have the advantages of single-sided welding and double-sided forming, convenient operation when welding vertically in all positions, high welding efficiency, strong arc blowing force, and more suitable for complex environments. They are widely used in the welding of large-diameter transmission pipelines in petroleum, chemical, and electric power industries.
[0004] At present, the existing cellulose welding rods have technical problems such as insufficient arc blowing force, poor stability and poor weld mechanical properties during use. Based on this, it is necessary to develop new cellulose welding rods to meet market demand. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the first object of the present invention is to provide a high-performance cellulose electrode coating with excellent welding process and beautiful weld formation.
[0006] The second object of the present invention is to provide a method for preparing a high-performance cellulose welding rod with simple steps.
[0007] The third object of the present invention is to provide a high-performance cellulose welding rod having excellent mechanical properties.
[0008] The first object of the present invention is achieved by the following technical solution:
[0009] A high-performance cellulose electrode coating comprises the following raw materials in parts by weight: 22-27 parts of microcrystalline cellulose, 1-5 parts of modified carboxymethyl cellulose, 0.5-3 parts of konjac powder, 3-5 parts of potassium hexatitanate, 10-17 parts of high-carbon ferromanganese, 4-8 parts of magnesium oxide, 3-5 parts of rutile, 1-3 parts of quartz, 2-5 parts of titanium carbide, and 15-20 parts of water glass;
[0010] The preparation process of the modified carboxymethyl cellulose is as follows:
[0011] (1) adding carboxymethyl cellulose to an ethylene glycol solution, then adding polyethylene and ferric chloride, heating and stirring to react, and cooling to room temperature after the reaction is completed to obtain a reaction solution;
[0012] (2) Adding polyethyleneimine to the reaction solution of step (1), heating and stirring to react, and separating and purifying to obtain modified carboxymethyl cellulose.
[0013] Furthermore, the dosage ratio of the carboxymethyl cellulose, polyethylene, ferric chloride, polyethyleneimine and ethylene glycol solution is 1g: 3-5g: 5-10g: 1-3g: 0.3-0.5L; and the concentration of the ethylene glycol solution is 65-80%.
[0014] Furthermore, the heating temperature in step (1) is 200-220° C., and the heating and stirring time is 10-15 h; the heating temperature in step (2) is 60-70° C., and the heating and stirring time is 5-10 h.
[0015] Furthermore, the konjac glucomannan content of the konjac flour is ≥75%, and the viscosity value is ≥20000 mPa·s.
[0016] Furthermore, the C mass content in the high carbon ferromanganese is ≥7%, and the Mn mass content is ≥80%; the TiO2 mass content in the rutile is ≥96.0%, the S mass content is ≤0.012%, and the P mass content is ≤0.015%.
[0017] Furthermore, the size of the microcrystalline cellulose is 50-70 nm; the water glass is potassium water glass, the modulus of the potassium water glass is 2.5-3, and the Baume degree is 38-40°Bé.
[0018] The second object of the present invention is achieved by the following technical solution:
[0019] A method for preparing a high-performance cellulose welding rod comprises the following steps:
[0020] According to the above ratio, microcrystalline cellulose, modified carboxymethyl cellulose, konjac flour, potassium hexatitanate, high carbon ferromanganese, magnesium oxide, rutile, quartz and titanium carbide are uniformly mixed to obtain a mixed powder, water glass is added to the mixed powder to obtain a coating, the coating is coated on the surface of the welding core, and the welding rod is obtained after drying.
[0021] Furthermore, the mass of the coating accounts for 28-35% of the total mass of the welding rod.
[0022] Furthermore, the drying temperature is 250-300° C. and the drying time is 1.5-2.5 h.
[0023] Furthermore, the welding core is a H08GX type welding core.
[0024] The third object of the present invention is achieved by the following technical solution:
[0025] A high-performance cellulose welding rod is prepared by adopting the preparation method of the high-performance cellulose welding rod.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The invention improves the components of the electrode coating, improves the stability and dispersibility of the carboxymethyl cellulose by modifying the carboxymethyl cellulose, and uses the modified carboxymethyl cellulose and konjac powder in combination to stabilize the arc, generate gas and plasticize, thereby achieving the purpose of enhancing the blowing force of the electrode arc, improving the thermal stability and improving the mechanical properties of the weld. DETAILED DESCRIPTION
[0028] The technical scheme of the present invention is further explained below in conjunction with specific examples and comparative examples. In the following examples and comparative examples, the raw materials and preparation methods used are conventional materials and techniques in the art unless otherwise specified.
[0029] (I) Embodiment
[0030] Example 1
[0031] Embodiment 1 provides a high-performance cellulose electrode coating, which is composed of the following raw materials in parts by weight: 24 parts of microcrystalline cellulose (size is 50-70nm), 3 parts of modified carboxymethyl cellulose, 2 parts of konjac flour (konjac glucomannan content is 75%, viscosity value is ≥20000mPa·s), 4 parts of potassium hexatitanate, 15 parts of high carbon ferromanganese (C mass content is 7%, Mn mass content is 80%), 6 parts of magnesium oxide, 4 parts of rutile (TiO2 mass content is ≥96.0%, S mass content is ≤0.012%, P mass content is ≤0.015%), 2 parts of quartz, 3 parts of titanium carbide, and 17 parts of potassium water glass (modulus is 3, Baume degree is 40°Bé).
[0032] The specific preparation process of the modified carboxymethyl cellulose is as follows:
[0033] (1) According to the usage ratio of carboxymethyl cellulose, polyethylene, ferric chloride, polyethyleneimine, and ethylene glycol solution of 1g:4g:7g:2g:0.4L, the above raw materials are weighed, carboxymethyl cellulose is added to the ethylene glycol solution, and then polyethylene and ferric chloride are added, and the mixture is heated and stirred at 210°C for 14 hours. After the reaction is completed, the reaction solution is cooled to room temperature to obtain a reaction solution;
[0034] (2) Add polyethyleneimine to the reaction solution of step (1), heat and stir at 65° C. for 7 h, and after the reaction is completed, cool the reaction solution to room temperature and centrifuge it, wash it to neutrality, and dry it to obtain modified carboxymethyl cellulose.
[0035] Example 1 also provides a method for preparing a high-performance cellulose welding rod, and the specific preparation process is as follows:
[0036] According to the above ratio, microcrystalline cellulose, modified carboxymethyl cellulose, konjac flour, potassium hexatitanate, high carbon ferromanganese, magnesium oxide, rutile, quartz and titanium carbide are uniformly mixed to obtain a mixed powder, potassium water glass is added to the mixed powder to obtain a coating, the coating is coated on the surface of the H08GX welding core, and the welding rod is obtained after drying at 260°C for 2 hours. The coating mass accounts for 32% of the total mass of the entire welding rod.
[0037] Example 1 also provides a high-performance cellulose welding rod, which is prepared by the above-mentioned preparation method of the high-performance cellulose welding rod.
[0038] Example 2
[0039] Example 2 provides a high-performance cellulose electrode coating, which is composed of the following raw materials in parts by weight: 22 parts of microcrystalline cellulose (size 50-70nm), 1 part of modified carboxymethyl cellulose, 0.5 parts of konjac flour (konjac glucomannan content 75%, viscosity value ≥20000mPa·s), 3 parts of potassium hexatitanate, 10 parts of high carbon ferromanganese (C mass content 7%, Mn mass content 80%), 4 parts of magnesium oxide, 3 parts of rutile (TiO2 mass content ≥96.0%, S mass content ≤0.012%, P mass content ≤0.015%), 1 part of quartz, 2 parts of titanium carbide, and 15 parts of potassium water glass (modulus 2.7, Baume degree 40°Bé).
[0040] The specific preparation process of the modified carboxymethyl cellulose is as follows:
[0041] (1) According to the usage ratio of carboxymethyl cellulose, polyethylene, ferric chloride, polyethyleneimine, and ethylene glycol solution of 1 g: 3 g: 5 g: 1 g: 0.3 L, the above raw materials are weighed, carboxymethyl cellulose is added to the ethylene glycol solution, and then polyethylene and ferric chloride are added, and the mixture is heated and stirred at 200° C. for 15 h. After the reaction is completed, the reaction solution is cooled to room temperature to obtain a reaction solution;
[0042] (2) Add polyethyleneimine to the reaction solution of step (1), heat and stir at 60° C. to react for 10 h. After the reaction is completed, cool the reaction solution to room temperature and centrifuge it, wash it to neutrality, and dry it to obtain modified carboxymethyl cellulose.
[0043] Example 2 also provides a method for preparing a high-performance cellulose welding rod, and the specific preparation process is as follows:
[0044] According to the above ratio, microcrystalline cellulose, modified carboxymethyl cellulose, konjac flour, potassium hexatitanate, high carbon ferromanganese, magnesium oxide, rutile, quartz and titanium carbide are uniformly mixed to obtain a mixed powder, potassium water glass is added to the mixed powder to obtain a coating, the coating is coated on the surface of the H08GX welding core, and the welding rod is obtained after drying at 300°C for 1.5 hours, and the coating mass accounts for 28% of the total mass of the entire welding rod.
[0045] Example 2 also provides a high-performance cellulose welding rod, which is prepared by the above-mentioned preparation method of the high-performance cellulose welding rod.
[0046] Example 3
[0047] Example 3 provides a high-performance cellulose electrode coating, which is composed of the following raw materials in parts by weight: 27 parts of microcrystalline cellulose (size 50-70nm), 5 parts of modified carboxymethyl cellulose, 3 parts of konjac flour (konjac glucomannan content 75%, viscosity value ≥20000mPa·s), 5 parts of potassium hexatitanate, 17 parts of high carbon ferromanganese (C mass content 7%, Mn mass content 80%), 8 parts of magnesium oxide, 5 parts of rutile (TiO2 mass content ≥96.0%, S mass content ≤0.012%, P mass content ≤0.015%), 3 parts of quartz, 5 parts of titanium carbide, and 20 parts of potassium water glass (modulus 2.5, Baume degree 38°Bé).
[0048] The specific preparation process of the modified carboxymethyl cellulose is as follows:
[0049] (1) according to the amount ratio of carboxymethyl cellulose, polyethylene, ferric chloride, polyethyleneimine, and ethylene glycol solution of 1g:5g:10g:3g:0.5L, weigh the above raw materials, add carboxymethyl cellulose to the ethylene glycol solution, then add polyethylene and ferric chloride, heat and stir at 220°C for 15h, and after the reaction is completed, cool the reaction solution to room temperature to obtain a reaction solution;
[0050] (2) Add polyethyleneimine to the reaction solution of step (1), heat and stir at 70° C. to react for 5 h. After the reaction is completed, cool the reaction solution to room temperature and centrifuge it, wash it to neutrality, and dry it to obtain modified carboxymethyl cellulose.
[0051] Example 3 also provides a method for preparing a high-performance cellulose welding rod, and the specific preparation process is as follows:
[0052] According to the above ratio, microcrystalline cellulose, modified carboxymethyl cellulose, konjac flour, potassium hexatitanate, high carbon ferromanganese, magnesium oxide, rutile, quartz and titanium carbide are uniformly mixed to obtain a mixed powder, potassium water glass is added to the mixed powder to obtain a coating, the coating is coated on the surface of the H08GX welding core, and the welding rod is obtained after drying at 250°C for 2.5 hours, and the coating mass accounts for 35% of the total mass of the entire welding rod.
[0053] Example 3 also provides a high-performance cellulose welding rod, which is prepared by the above-mentioned preparation method of the high-performance cellulose welding rod.
[0054] (II) Comparative Example
[0055] Comparative Example 1
[0056] Comparative Example 1 provides a welding rod coating, which is composed of the following raw materials in parts by weight: 24 parts of microcrystalline cellulose (size 50-70nm), 3 parts of carboxymethyl cellulose, 2 parts of konjac flour (konjac glucomannan content 75%, viscosity value ≥20000mPa·s), 4 parts of potassium hexatitanate, 15 parts of high carbon ferromanganese (C mass content 7%, Mn mass content 80%), 6 parts of magnesium oxide, 4 parts of rutile (TiO2 mass content ≥96.0%, S mass content ≤0.012%, P mass content ≤0.015%), 2 parts of quartz, 3 parts of titanium carbide, and 17 parts of potassium water glass (modulus 3, Baume degree 40°Bé).
[0057] Comparative Example 1 also provides a method for preparing a welding rod, and the process is the same as that of Example 1.
[0058] Comparative Example 1 also provides a welding rod, which is prepared by the above preparation method.
[0059] Comparative Example 2
[0060] Comparative Example 2 provides a welding rod coating, which is composed of the following raw materials in parts by weight: 24 parts of microcrystalline cellulose (size 50-70nm), 2 parts of konjac flour (konjac glucomannan content 75%, viscosity value ≥20000mPa·s), 4 parts of potassium hexatitanate, 15 parts of high carbon ferromanganese (C mass content 7%, Mn mass content 80%), 6 parts of magnesium oxide, 4 parts of rutile (TiO2 mass content ≥96.0%, S mass content ≤0.012%, P mass content ≤0.015%), 2 parts of quartz, 3 parts of titanium carbide, and 17 parts of potassium water glass (modulus 3, Baume degree 40°Bé).
[0061] Comparative Example 2 also provides a method for preparing a welding rod, and the process is the same as that of Example 1.
[0062] Comparative Example 2 also provides a welding rod, which is prepared by the above preparation method.
[0063] Comparative Example 3
[0064] Comparative Example 3 provides a welding rod coating, which is composed of the following raw materials in parts by weight: 24 parts of microcrystalline cellulose (size 50-70nm), 5 parts of konjac flour (konjac glucomannan content 75%, viscosity value ≥20000mPa·s), 4 parts of potassium hexatitanate, 15 parts of high carbon ferromanganese (C mass content 7%, Mn mass content 80%), 6 parts of magnesium oxide, 4 parts of rutile (TiO2 mass content ≥96.0%, S mass content ≤0.012%, P mass content ≤0.015%), 2 parts of quartz, 3 parts of titanium carbide, and 17 parts of potassium water glass (modulus 3, Baume degree 40°Bé).
[0065] Comparative Example 3 also provides a method for preparing a welding rod, and the process is the same as that of Example 1.
[0066] Comparative Example 3 also provides a welding rod, which is prepared by the above preparation method.
[0067] Comparative Example 4
[0068] Comparative Example 4 provides a welding rod coating, which is composed of the following raw materials in parts by weight: 24 parts of microcrystalline cellulose (size is 50-70nm), 3 parts of modified carboxymethyl cellulose, 4 parts of potassium hexatitanate, 15 parts of high carbon ferromanganese (C mass content is 7%, Mn mass content is 80%), 6 parts of magnesium oxide, 4 parts of rutile (TiO2 mass content is ≥96.0%, S mass content is ≤0.012%, P mass content is ≤0.015%), 2 parts of quartz, 3 parts of titanium carbide, and 17 parts of potassium water glass (modulus is 3, Baume is 40°Bé).
[0069] Comparative Example 4 also provides a method for preparing a welding rod, and the process is the same as that of Example 1.
[0070] Comparative Example 4 also provides a welding rod, which is prepared by the above preparation method.
[0071] Comparative Example 5
[0072] Comparative Example 5 provides a welding rod coating, which is composed of the following raw materials in parts by weight: 24 parts of microcrystalline cellulose (size 50-70nm), 5 parts of modified carboxymethyl cellulose, 4 parts of potassium hexatitanate, 15 parts of high carbon ferromanganese (C mass content 7%, Mn mass content 80%), 6 parts of magnesium oxide, 4 parts of rutile (TiO2 mass content ≥96.0%, S mass content ≤0.012%, P mass content ≤0.015%), 2 parts of quartz, 3 parts of titanium carbide, and 17 parts of potassium water glass (modulus 3, Baume degree 40°Bé).
[0073] Comparative Example 5 also provides a method for preparing a welding rod, and the process is the same as that of Example 1.
[0074] Comparative Example 5 also provides a welding rod, which is made using the above preparation method.
[0075] The properties of the welding rods prepared in Examples 1-3 and Comparative Examples 1-5 are tested below.
[0076] Welding experiments were conducted on the welding rods prepared in Examples 1-3 and Comparative Examples 1-5. The welding power source was DC or AC, and the welding current was 90-100A.
[0077] (1) The welding process performance of the welding rod is tested, and the welding process record is shown in Table 1.
[0078] (2) Mechanical properties of welds: The yield strength, tensile strength, elongation after fracture and -30°C impact properties of each group of cladding metals were tested in accordance with GB / T2652-2008 “Tensile test methods for welds and deposited metals”. The results are shown in Tables 2-3, where Table 2 is the DC welding mechanical properties and Table 3 is the AC welding mechanical properties.
[0079] Table 1
[0080]
[0081]
[0082] Table 2 DC welding mechanical properties
[0083]
[0084]
[0085] Table 3 AC welding mechanical properties
[0086]
[0087] It can be seen from Table 1 that the welding rods prepared in Examples 1-3 have good weld backside formation under DC or AC welding conditions, and no pores, slag inclusions, etc., which means that the welding rods prepared in the present invention have excellent welding technology.
[0088] Compared with embodiment 1-3, comparative example 1 adopts carboxymethyl cellulose to replace the welding rod that modified carboxymethyl cellulose makes under direct current or alternating current welding condition, and the weld back side is well formed, and there are phenomena such as pores, slag inclusions; the welding rod that comparative examples 2-5 make under direct current or alternating current welding condition, the weld back side is poorly formed, and there are phenomena such as pores, slag inclusions. And comparative example 2 saves modified carboxymethyl cellulose when preparing welding rod, comparative example 3 saves modified carboxymethyl cellulose when preparing welding rod, increases the consumption of konjac powder, comparative example 4 saves konjac powder when preparing welding rod, comparative example 5 saves konjac powder when preparing welding rod, increases the consumption of modified carboxymethyl cellulose. As can be seen from the above, when modified carboxymethyl cellulose and konjac powder are used in combination, the weld back side is better formed, and there are no phenomena such as pores, slag inclusions, which also illustrates that the welding rod made by the present invention can improve the arc blowing force and stability of welding rod.
[0089] As shown in Table 2-3, the welding rods prepared in Examples 1-3 have excellent mechanical properties under direct current or alternating current welding conditions. Compared with Examples 1-3, the mechanical properties of the welding rods prepared in Comparative Example 1 are reduced. Compared with Examples 1-3, the mechanical properties of the welding rods prepared in Comparative Example 2-5 are significantly reduced. Further analysis shows that Comparative Example 2-5 adjusts the amount of modified carboxymethyl cellulose or konjac flour, which leads to the reduction of various mechanical properties. As shown above, the use of modified carboxymethyl cellulose and konjac flour can effectively improve the various mechanical properties of weld metal.
[0090] In summary, the combination of modified carboxymethyl cellulose and konjac flour has the effects of arc stabilization, gasification and plasticization, thereby achieving the purpose of enhancing the blowing force of the electrode arc, improving thermal stability and improving the mechanical properties of the weld.
[0091] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A high performance cellulose electrode coating, characterized in that: The invention comprises the following raw materials in parts by weight: 22-27 parts of microcrystalline cellulose, 1-5 parts of modified carboxymethyl cellulose, 0.5-3 parts of konjac powder, 3-5 parts of potassium hexatitanate, 10-17 parts of high carbon ferromanganese, 4-8 parts of magnesium oxide, 3-5 parts of rutile, 1-3 parts of quartz, 2-5 parts of titanium carbide and 15-20 parts of water glass; The preparation process of the modified carboxymethyl cellulose is as follows: (1) adding carboxymethyl cellulose to an ethylene glycol solution, then adding polyethylene and ferric chloride, heating and stirring to react, and cooling to room temperature after the reaction is completed to obtain a reaction solution; (2) adding polyethyleneimine to the reaction solution of step (1), heating and stirring to react, and separating and purifying to obtain modified carboxymethyl cellulose; The konjac glucomannan content of the konjac refined flour is ≥75%, and the viscosity value is ≥20000 mPa·s.
2. The high performance cellulose electrode coating according to claim 1, characterized in that: The dosage ratio of the carboxymethyl cellulose, polyethylene, ferric chloride, polyethyleneimine and ethylene glycol solution is 1g: (3-5)g: (5-10)g: (1-3)g: (0.3-0.5)L; the concentration of the ethylene glycol solution is 65-80%.
3. The high performance cellulose electrode coating according to claim 1, characterized in that: The heating temperature in step (1) is 200-220° C., and the heating and stirring time is 10-15 h; the heating temperature in step (2) is 60-70° C., and the heating and stirring time is 5-10 h.
4. The high performance cellulose electrode coating according to claim 1, characterized in that: The high carbon ferromanganese has a C mass content of ≥7% and a Mn mass content of ≥80%; the rutile has a TiO2 mass content of ≥96.0%, a S mass content of ≤0.012%, and a P mass content of ≤0.015%.
5. The high performance cellulose electrode coating according to claim 1, characterized in that: The size of the microcrystalline cellulose is 50-70 nm; the water glass is potassium water glass, the modulus of the potassium water glass is 2.5-3, and the Baume degree is 38-40°Bé.
6. A method for preparing a high-performance cellulose welding rod, characterized in that: The following steps are involved: According to the ratio described in claim 1, microcrystalline cellulose, modified carboxymethyl cellulose, konjac flour, potassium hexatitanate, high carbon ferromanganese, magnesium oxide, rutile, quartz and titanium carbide are uniformly mixed to obtain a mixed powder, water glass is added to the mixed powder to obtain a coating, the coating is coated on the surface of the welding core, and the welding rod is obtained after drying.
7. The method for preparing the high-performance cellulose welding rod according to claim 6, characterized in that: The mass of the coating accounts for 28-35% of the total mass of the welding rod.
8. The method for preparing the high-performance cellulose welding rod according to claim 6, characterized in that: The drying temperature is 250-300° C. and the drying time is 1.5-2.5 hours.
9. A high performance cellulose welding rod, characterized in that: The preparation method is described in any one of claims 6 to 8.
Citation Information
Patent Citations
J422 welding electrode
CN103240546A
Alternating-current and direct-current dual-purpose high-blowing-force cellulose welding rod
CN112958939A